2020
DOI: 10.3390/insects11110811
|View full text |Cite
|
Sign up to set email alerts
|

Search for Alternative Control Strategies of Drosophila suzukii (Diptera: Drosophilidae): Laboratory Assays Using Volatile Natural Plant Compounds

Abstract: Drosophila suzukii (Diptera: Drosophilidae), is native to southeastern Asia and invaded Europe during the past decade. It causes serious economic damage in cherries and soft fruits. Control strategies rely on few insecticides with varying success. Due to environmental concern, the use of synthetic chemicals is restricted. Therefore, research effort is put into the quest for alternative substances applicable in chemical pest control. In laboratory assays, we tested 17 volatile plant compounds from different che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 94 publications
0
17
0
Order By: Relevance
“…Our phytochemical analyses revealed that the most frequent compounds found in these EOs were linalool (5.0 and 70.8%), neral (9.1 and 28.7%), geraniol (5.5 and 91.7%), geranial (22.1 and 44.6%), menthol (45.3 and 96.8%), and 1,8-cineole (36.8 and 40.1%). Although the chemical composition differs among the 19 selected EOs, there are reports of common functional groups of monoterpenes, such as α-pinene, citral, citronellal, citronellol, linalool, menthol, menthol, and 1,8-cineol, that have multiple chemical properties against D. suzukii such as toxicity, repellency, and deterrence of feed and oviposition [ 6 , 31 , 34 , 39 ]. It is also known that the efficacy of EOs on D. suzukii depends on the composition and proportions of the main substances, as demonstrated for C. verum [ 31 ] and Gaultheria fragrantima [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our phytochemical analyses revealed that the most frequent compounds found in these EOs were linalool (5.0 and 70.8%), neral (9.1 and 28.7%), geraniol (5.5 and 91.7%), geranial (22.1 and 44.6%), menthol (45.3 and 96.8%), and 1,8-cineole (36.8 and 40.1%). Although the chemical composition differs among the 19 selected EOs, there are reports of common functional groups of monoterpenes, such as α-pinene, citral, citronellal, citronellol, linalool, menthol, menthol, and 1,8-cineol, that have multiple chemical properties against D. suzukii such as toxicity, repellency, and deterrence of feed and oviposition [ 6 , 31 , 34 , 39 ]. It is also known that the efficacy of EOs on D. suzukii depends on the composition and proportions of the main substances, as demonstrated for C. verum [ 31 ] and Gaultheria fragrantima [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the chemical composition differs among the 19 selected EOs, there are reports of common functional groups of monoterpenes, such as α-pinene, citral, citronellal, citronellol, linalool, menthol, menthol, and 1,8-cineol, that have multiple chemical properties against D. suzukii such as toxicity, repellency, and deterrence of feed and oviposition [ 6 , 31 , 34 , 39 ]. It is also known that the efficacy of EOs on D. suzukii depends on the composition and proportions of the main substances, as demonstrated for C. verum [ 31 ] and Gaultheria fragrantima [ 40 ]. Likewise, the interactions of minority constituents contained in EOs have been reported to have synergistic action, providing a significant increase in the effectiveness of formulations for arthropod pests [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, other studies showed that kinetin reduced the egg-laying capacity of the fruit flies (Kaur and Rup, 2002). Apart from PGRs, various plant-derived compounds had been reported to detrimentally inhibit the oviposition efficiency of some insect pests, such as S. littoralis by Nerolidol (Hamadah et al, 2020) or Farnesol (Hamadah et al, 2021); S. oryzae by Eugenol (Chaubey, 2016); the melon worm Diaphania hyalinata by Rotenone (Silva et al, 2016) and the vinegar fly Drosophila suzukiiby citral and eugenol (Eben et al, 2020).…”
Section: Ii1 Prohibited Oviposition Efficiency By 6-bamentioning
confidence: 99%